تمثيلات المهاجر وتبئير الهامش في رواية أدغال البحر والسراب لمصطفى ولد يوسف. (مجلة الواحات للبحوث والدراسات, 2023)
ملخص:     حاولنا في هذا المقال دراسة تمثيلات المهاجر في رواية أدغال البحر والسراب لمصطفى ولد يوسف، وخطورة الهجرة غير الشرعية على الفئات الاجتماعية التي تعاني التهميش في المجتمع الجزائري ، من خلال مدركات الهجرة وأبعاد التمثيل السردي، في الخطاب الروائي، وتقصينا فكرة الهامش والمركز، وتداعيات الهجرة وأسبابها الحتمية، المفروضة على المهاجرين، سواء كانوا من الطبقة المثقفة أو كشخصية طفولية تسعى للتحرر من قيد الأسرة، أو امرأة مضطهدة عانت من خيبات الأمل، فتكفل الكرونوتوب الفانتاستيكي بإبراز معالم التاريخ والمتخيل، وتفكيك الصورة النمطية بين الأنا/المتحضر، والآخر/ المتوحش.كلمات دالة : التمثيل السردي، الهامش، المركز، المهاجر، السارد.                                                                   Abstract:In this article, we tried to study the representations of the immigrant in the novel Jungles of the Sea and the Mirage by Mustafa Ould Youssef, and the danger       of illegal immigration to the social groups that suffer marginalization in Algerian society, through the perceptions of migration and the dimensions of narrative representation, in the fictional discourse, and we investigated the idea of the margin and the center, and the repercussions of migration and its causes The inevitability imposed on immigrants, whether they were from the educated class or as a childish figure seeking liberation from the constraint of the family, or an oppressed woman who suffered from disappointments. The fantastic chronotope ensures highlighting the features of history and the imaginary, and dismantling the stereotype between the ego / civilized and the other / savage.                     Key words: Narrative representation, margin, center, emigrant, narrator